The Analysis of the Feedback from Primary School Teachers on Multimedia Applications: Ukrainian Case-Study - Herasymova, Olena; Osvita.Dity.Maibutnie (ODM) (Zenodo, 2025)
The dataset was created as part of research work aimed at analyzing feedback on cross-media projects from primary school teachers. Data from the longitudinal survey were collected from September 11, 2023, to April 10, 2024. The extracted information from these data was used to measure the level of teacher engagement and awareness in Ukraine about digital learning materials assessing.